2017
DOI: 10.1371/journal.pone.0171922
|View full text |Cite
|
Sign up to set email alerts
|

Tumor stroma with senescence-associated secretory phenotype in steatohepatitic hepatocellular carcinoma

Abstract: Senescence secretome was recently reported to promote liver cancer in an obese mouse model. Steatohepatitic hepatocellular carcinoma (SH-HCC), a new variant of HCC, has been found in metabolic syndrome patients, and pericellular fibrosis, a characteristic feature of SH-HCC, suggests that alteration of the tumor stroma might play an important role in SH-HCC development. Clinicopathological characteristics and tumor stroma showing senescence and senescence-associated secretory phenotype (SASP) were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 29 publications
(33 reference statements)
1
41
1
Order By: Relevance
“…Yoshimoto et al related these findings to an increase in gut microbiota population, which produces the DNA‐damaging metabolite deoxycholic acid, promoting SASP in HSCs . Moreover, in human NASH‐related HCC, cancer‐associated fibroblasts and nontumoral HSCs demonstrated increased expression of senescence markers and SASP markers compared with those deriving from conventional HCC . Further mechanistic studies are needed to elucidate the role of senescence in NASH‐associated HCC.…”
Section: The Role Of Senescence In Nafld/nashmentioning
confidence: 99%
“…Yoshimoto et al related these findings to an increase in gut microbiota population, which produces the DNA‐damaging metabolite deoxycholic acid, promoting SASP in HSCs . Moreover, in human NASH‐related HCC, cancer‐associated fibroblasts and nontumoral HSCs demonstrated increased expression of senescence markers and SASP markers compared with those deriving from conventional HCC . Further mechanistic studies are needed to elucidate the role of senescence in NASH‐associated HCC.…”
Section: The Role Of Senescence In Nafld/nashmentioning
confidence: 99%
“…Normally, SASP factors target senescent cells (SNCs) for removal by the immune system, clearing adjacent, nonsenescent preneoplastic cells in the process and therefore providing tumor-suppressive benefits that are supe-rior to apoptosis (6). However, long-term persistence of SNCs and their secretome drives cancer, atherosclerosis 7, and other major age-related diseases, in addition to aging itself (8)(9)(10). The solidifying link between SNCs, cardiovascular aging, and CVD depends on four lines of evidence.…”
Section: Introductionmentioning
confidence: 99%
“…It was noted that around 60% (14 of 22) SH-HCCs was associated with one more known risk factor for non-alcoholic fatty liver disease (NAFLD) [10] . The association with and NAFLD and metabolic syndrome was consolidated in other studies [13,14] . While most studies suggested a link of fatty liver disease with this subtype, in 2015 Yeh et al [15] looked at a series of SH-HCC and identified a group of patients without any underlying causes for metabolic disease.…”
Section: Sh-hccmentioning
confidence: 86%
“…Immunohistochemical expression of serum amyloid A and CRP was significantly higher in this subtype than conventional HCC as revealed by another study [16] . It was also found that the cancer-associated fibroblasts in SH-HCC more frequently expressed senescence-associated secretory phenotype by immunohistochemical staining [14] . On genetic and genomic levels, SH-HCC was shown to associate with IL6/JAK/STAT pathway activation, as well as wild type CTNNB1 [8,17] and TP53 [8] .…”
Section: Sh-hccmentioning
confidence: 88%